Sosialisasi Dampak Pernikahan Dini Sebagai Upaya Peningkatan Kesadaran Remaja Terhadap Pentingnya Berperilaku Sehat dan Bertanggung Jawab di SMA Negeri 9 Kendari Tahun 2025 - Sartiah Yusran; I Putu Sudayasa; Ardiansyah Adi Putra; Cici Wulandari Asmun; Fadilatulsyam; Herli Anita; Ida Royani Sampulawa; Isnaeni Salamiyah; Laode Muh. Al-Kasran Razak (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2026)
Background: Early marriage remains a social issue that negatively affects adolescents’ health, education, and overall well-being. Limited understanding among adolescents regarding the risks of early marriage highlights the need for structured and targeted educational interventions within the school setting. Objective: This activity aimed to increase adolescents’ knowledge and awareness of the definition, causes, and impacts of early marriage, while encouraging students to prioritize education and psychological readiness before entering marriage. Methods: This community service activity employed a descriptive design with an educational approach through interactive counseling on early marriage involving 35 twelfth-grade students at Kendari State High School 9. Data were collected through participatory observation and group discussions, and analyzed using descriptive qualitative methods. Results: The findings showed that students participated enthusiastically, actively engaged in discussions, and demonstrated an improved understanding of the health, psychological, social, and educational impacts of early marriage. In addition, students exhibited increased awareness of the importance of adopting healthy and responsible attitudes toward reproductive health. Conclusion: The socialization activity was effective in fostering critical attitudes and raising students’ awareness of the negative impacts of early marriage. Therefore, it has the potential to serve as a preventive effort to reduce child marriage and prevent the phenomenon of “children giving birth to children” in the school environment.